Thermal Response and Mechanical Behaviors of Compact Basalts Induced by Microwave Irradiation. (5th September 2022) - Zhang, Xiao-Wu; Xu, Jin-Hai; Chen, Liang; Cao, Yue; Sun, Lei; Shaikh, Faiz
Abstract : Microwave pretreatment could be an invaluable method to improve the efficiency of the rock breakage in the excavation and comminution operations. To investigate the influence of microwave irradiation on the thermal response and mechanical behavior of compact rocks, a series of physical and mechanical experiments were conducted on the nontreated and treated basalts. The mineral compositions of the basalts were obtained by X-ray diffraction (XRD) test. Scanning electron microscope (SEM) images and geological sketch were utilized to analyze the propagation pattern of the microcracks and macrofractures caused by the microwave irradiation. High power density microwave can induce the complication of the microcracks and exchange the pattern of the macrofracture network. Based on the uniaxial compression strength (UCS) test, the mechanical performance of the basalts was evidently reduced with the increase of the microwave power and exposure time. The experimental results prove that microwave-assisted method has significant potential application to preweakening rocks in civil and mining engineering.